Design of Data Warehouse for Minimarket’s Sales Information Using Tabular Models - I Gusti Ngurah Agung Jaya Sasmita; Made Sudarma; Dewa Made Wiharta (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2020)
Alongside with development of technology, more business need support of business intelligence tools to transform its data in a meaningful way which is accumulated rapidly in every transaction occurred. In order to achieved that, data warehouse with its online analytical processing (olap) can be considered as a solution. One tools for creating an olap from data warehouse is SSAS. This tools consist of two models, first one is multidimensional models or can be said the traditional one and the new one is tabular models. One best feature that tabular models give is the time needed for building it. The tabular models does not require the data in format of fact and dimension tables so reduce the time to change particular data into some scheme (star or snowflake). Hence, the purpose of this research is to design a data warehouse for minimarket’s sales information using the advantage of tabular modeling for creating the analysis. Its also known that, the data analysis created using tabular, support reporting application such as pivot table excel, so the user not need to create a new application for reporting analysis